Mutation hotspots due to sunlight in the p53 gene of nonmelanoma skin cancers. - Ziegler, A (1993)
To identify the sites in the p53 tumor suppressor gene most susceptible to carcinogenic mutation by sunlight, the entire coding region of 27 basal cell carcinomas (BCCs) of the skin was sequenced. Fifty-six percent of tumors contained mutations, and these were UV-like: primarily CC-->TT or C-->T changes at dipyrimidine sites. Such mutations can alter more than half of the 393 amino acids in p53, but two-thirds occurred at nine sites at which mutations were seen more than once in BCC or in 27 previously studied squamous cell carcinomas of the skin. Seven of these mutation hotspots were specific to skin cancers. Internal-cancer hotspots not located at dipyrimidine sites were not mutated in skin cancers; moreover, UV photoproducts were absent at these nucleotides. The existence of hotspots altered the process of inactivating p53 in BCC compared to other cancers: allelic loss was rare, but 45% of the point mutations were accompanied by a second point mutation on the other allele. At least one of each pair was located at a hotspot. Sunlight, acting at mutation hotspots, appears to cause mutations so frequently that it is often responsible for two genetic events in BCC development.